{ x + 3y = 12,
{ 4x + 2y = -12,
(выделяем Х из 1 ур-ия):
{ x = 12 - 3у,
{ 4x + 2y = -12,
подставим во 2 ур-ие значение Х из 1 ур-ия:
4 * (12 - 3у) + 2у =-12,
48 - 12у + 2у = -12,
-10у = -12 - 48,
10у = 60,
у = 6,
х = 12 - 3у = 12 - 3*6 = 12 - 18 = -6,
(выделяем У из 2 ур-ия):
{ x + 3y = 12,
{ 2y = -12 - 4х,
{ x + 3y = 12,
{ у = -6 - 2х,
подставим в 1 ур-ие значение У из 2 ур-ия:
х + 3 * (-6 - 2х) = 12,
х -18 - 6х = 12,
-5х = 12 + 18,
-5х = 30,
х = -6,
у = -6 - 2х = -6 - 2*(-6) = -6 + 12 = 6,
ответ: (-6; 6)
t1=? ч
t2=? ч
V1=60 км/ч
V2=40 км/ч
А=300км
t1=300:60=5
t2=300:40=75
Пошаговое объяснение: